Practical Rationality and Moral Education in Alasdair MacIntyre’s Thought - Renani, Ali Abedi (RESEARCH TRENDS IN HUMANITIES Education & Philosophy, 2017)
MacIntyre holds that there is no practical reasoning capacity for human beings independent of his training and upbringing in moral traditions. Human beings should acquire moral virtues by following moral exemplars before being able to reason about them. MacIntyre’s position here approaches the virtue ethics view, which emphasizes the role of moral training and habituation in acquiring the capacity for practical reasoning. This position is at odds with the Kantian view according to which morality is a matter of practical and rule-based reasoning, which is independent of moral traditions; and in fact, serves as a measure for the evaluation of these traditions.